Property ( k) of Orlicz Sequence Spaces - ZUO Ming-xia; PENG Li-na (Journal of Harbin University of Science and Technology)
Property ( k) is an important geometric property in Banach spaces，and it is closely associated with fixed point property． By the geometric theory of Banach spaces and Orlicz spaces， we investigated the characterization for property( k) in a special class of Banach spaces-Orlicz sequence spaces． Criteria for property ( k) in Orlicz sequence spaces equipped with both the Luxemburg norm and the Orlicz norm are given． As a corollary，the sufficient condition that this kind of spaces has weak fixed point property is obtained．